Social Media Utilization of Public Benefit Organizations During the COVID-19 Pandemic - Piotr Szamrowski; Marian Oliński (European Management Studies)
Purpose: The main purpose of the research was twofold. First, it was to assess the impact of the COVID-19 pandemic on the publishing activity of Polish public benefit organizations on Facebook. Second, to determine the impact of content published in a crisis situation on the public reaction. Design/methodology/approach: During the investigation, the financial reports of public benefit organizations were analyzed. Farther the basic parameters of the organization’s Facebook profile and the content published on Facebook were analyzed (1025 organizations were covered by the research). From the reports, financial data of organizations has been collected. Both in 2020 and in 2021, posts of the same organizations were analyzed. Findings: The Covid-19 pandemic did not have a significant impact on the publishing activity of the surveyed organizations. Although interest in the Facebook profile of organizations during the Covid-19 pandemic increased, the results indicate that Facebook’s potential in the crisis stage was only used to a small extent. Research limitations/implications: The research is limited to one social networking site – Facebook. It would also be worth scrutinizing other social media sites (e.g. by comparative analysis). Originality/value: The paper fills a research gap regarding the behavior of non-profit organizations concerning the utilization of social media during the crisis consisting in losing direct contact with the public and the inability to operate in an offline environment (due to the lockdown). It shows what opportunities exist in such situations in social media and how the managers of non-profit organizations could use them for the benefit of the organizations they handle.